(untitled) (Annals of Medical Research, 2023)
Aim: The most important cause of insulin resistance(IR) is obesity. Abdominal adiposity(AA) is more important than general obesity in IR formation. The aim of this study is to evaluate waist circumference (WC), waist-hip ratio (WHR) and waist-length ratio (WLR) as the AA markers, and to question their predictive properties in IR. Materials and Methods: Individuals diagnosed with IR were retrospectively examined. Seventy patients between 20-65 ages without systemic disease and drug use were included in the study. The patients were evaluated in terms of age, gender, and obesity grades. They were divided into the risk groups according to WC, WHR, WLR and compared each other in terms of HOMA-IR levels. Results: Of the cases 78.6% were female and 21.4% were male. The mean age was 43.04 years. The mean HOMA-IR level was 5.38. Severe obesity was in 35(50%) patients. WC, in 87.2% of women 60% of men, WHR, in 65.4% of women 93.3% of men, and WLR, in 98.1% of women 93.3% of men were high. HOMA-IR level was found to be statistically different in the WLR risky group compared to the others (p<0.05). WLR was more significant and indicated IR with 70% sensitivity and 80% specificity with a HOMA IR level of 3.03 and above. Conclusion: WLR is a stronger predictor than WC and WHR in all obesity grades for IR. It can be preferred as a powerful predictor for the risk assessment of abdominal obesity and IR status.